Numerical Analysis Of Polymer Melts Flow Behaviour In Grooved Channel - Rajenthiren, Sharaneish (Universiti Sains Malaysia, 2022)
The effect of inlet pressure, pitch size, and varied mould channel on the flowability of the propylene are studied in terms of the velocity, flow rate, volume of the propylene in the mould, and ratio of the propylene to the total mixture. The study was conducted by using the Computational Fluid Dynamic (CFD) simulation software, ANSYS Fluent. The main focus of this project is to compare the flowability of the propylene in the different mould channels. Based on the simulation, the flow of propylene exhibits a proper flow when the inlet pressure is set at 25kPa. The volume of the propylene in the mould was the highest which indicates less air cavity is formed during the simulation. Meanwhile, when the pitch size is increased, the volume of propylene in the mould increases too. However, the volume of propylene drops after the pitch size is increased to 150mm due to pressure drop during the simulation. The different grooves in the channel affect the flowability of the propylene. For an instance the triangular channel allows more volume of propylene to fill up the mould as compared with circular and rectangular grooved channels as the velocity of the propylene is lowest in the triangular grooved channel, thereby improving the flowability of the propylene.